SGLT2 inhibitors: A revolution in therapeutics of a major Non-Communicable Disease - Muhammad Sami Khan (Journal of the Pakistan Medical Association, 2021)
Pakistan is facing an exorbitant burden of Non-communicable diseases among which Cardiovascular diseases are the most prominent which has not only caused mortality but also posed a big threat on weakened economy and health care system of the country. Amidst of this growing crisis, Sodium glucose co-transporter 2 (SGLT2) inhibitors emerge as a ray of hope by reducing simultaneously the complication and health care expenditure associated with the management of this major mortality-bringing Non-communicable disease. SGLT2 inhibitors, including Dapagliflozin and Empagliflozin, are evidence-based standardized novel anti-diabetic agents tested in cardiovascular outcome trials namely DAPA-HF and EMPEROR-Reduced, when added to standard care in heart failure patients with reduced ejection fraction, provides breakthrough heart failure outcomes and also addresses massive health care expenditures. This novel finding provides an impetus to promote its beneficial effects among health care providers and early implementation. Continuous....